IMPLEMENTASI SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU (PPDB) DI SMP NEGERI 1 PALLANGGA KABUPATEN GOWA - Ratika Nengsih; Rosmiati Rosmiati; Andi Fadillah A Natsir (IAI Al-Mawaddah Warrahmah Kolaka, 2023)
The policies made in the Admission of New Students with the Zoning system are contained in the Education and Culture Basic Law Number 44 of 2019 for schools at the elementary, junior high and high school levels. This policy applies to public schools and not to private schools. The purpose of establishing a zoning system policy in accepting new students is to equalize the quality of education, which so far has relied only on urban areas or is prominent in certain schools. Various problems arose. From the lack of public understanding of the existence of a zoning system to the fact that there are still people who do not know about the new regulations. From the organizers themselves, the problems that arose were drastic changes in the program and learning process, resulting in a decrease in the number and achievements of students as well as other problems. Therefore, this study adopted the research title on the Implementation of the Zoning System in the Implementation of New Student Admissions (PPDB) at SMP Negeri 1 Pallangga, Gowa Regency. This type of research is descriptive qualitative with a phenomenological approach. The research focus is determined by random technique. By using observation instruments, interviews and documentation which are then analyzed using triangulation. From the research results, the zoning system itself consists of 4 acceptance pathways, including: the zoning pathway, namely the distance where prospective students live within the school zoning radius, which is a maximum of 15 km and students who are in the school zoning must be accepted at least 50%, this achievement path marked in the form of a charter/certificate given to prospective students such as competitions, school exam scores with a maximum quota of 30%, affirmation pathways for prospective students who have low economic conditions marked by being registered as a family hope program and other government programs even though it is only there is a minimum quota of 15% and the mutation path / transfer of parents with a quota of only 5%. Therefore, to assess the feasibility of implementing the PPDB zoning program at SMP Negeri 1 Pallangga Gowa, the model used is George Edward III with 4 criteria, namely, communication, resources, disposition, implementing bureaucratic structure. So from the results of the research, SMP Negeri 1 Pallangga Gowa as the implementer has implemented PPDB with a good and maximum zoning system.